3D-printed scaffolds with synergistic effect of hollow-pipe structure and bioactive ions for vascularized bone regeneration. (August 2017) - Zhang, Wenjie; Feng, Chun; Yang, Guangzheng; Li, Guanglong; Ding, Xun; Wang, Shaoyi; Dou, Yuandong; Zhang, Zhiyuan; Chang, Jiang; Wu, Chengtie; Jiang, Xinquan
Abstract: Segmental bone regeneration remains a considerable challenge due to the associated low degree of vascularization. To solve this problem, in this study, hollow-pipe-packed silicate bioceramic (BRT-H) scaffolds are fabricated using a coaxial three-dimensional (3D) printing technique. Based on a modified core/shell printer nozzle and a modulated viscoelastic bioceramic paste, hollow struts with an external diameter of 1 mm and internal dimeter of 500 μm can be directly printed, yielding a compressive strength of the BRT-H scaffolds as high as 26 MPa. Apart from the effects on osteogenesis, the bioactive ions released from the BRT scaffolds can also facilitate angiogenesis via inducing endothelial cell migration. More importantly, the hollow pipes not only significantly promote the rapid infiltration of host blood vessels into the channels but also exhibit great advantages for the delivery of stem cells and growth factors to further enhance tissue regeneration. When used for the regeneration of rabbit radius segmental defects, radiological and histological findings indicate that the BRT-H scaffolds can enhance early vascularization and later bone regeneration and remodeling. Taken together, the hollow pipes and the ionic products from BRT-H scaffolds have a synergistic effect on enhancing vascularized bone regeneration.